A Brief Review on Measuring Methods of Thermal Conductivity of Organic and Hybrid Thermoelectric Materials. (13th June 2019) - Wang, Hanfu; Chu, Weiguo; Chen, Guangming
Abstract: Organic and hybrid thermoelectric (OHT) materials have attracted increasing research interest over the past decade. Thermal conductivity measurement plays a critical role in evaluating and improving the thermoelectric performance of various types of these novel materials, ranging from bulks to low‐dimensional structures. Commonly used and newly developed techniques for thermal conductivity measurement, most of which have been applied to OHT materials in recent years, are reviewed. They are categorized as steady‐state methods, time‐domain methods, or frequency‐domain methods. The operating principles, merits and limitations, technical issues, and application examples for each technique are also discussed. Abstract : Commonly used and newly developed techniques for thermal conductivity measurement are reviewed. These techniques, most of which have been applied to organic and hybrid thermoelectric materials, including bulk, thin film, and nanostructured, in recent years, are categorized as steady‐state methods, time‐domain methods, or frequency‐domain methods.